Theory and practice in social innovations in the city of Rio de Janeiro, Brazil - Afonso, Rita de Cassia Monteiro; Kleine, Dorothea; Orsi-Tinoco, Gabriel (Revista de Administração da UFSM, 2022)
Purpose: This article reviews the literature on social innovation, also focusing on Latin American production, identifying how the contents dialogue with the reality of initiatives in the city of Rio de Janeiro, Brazil. Design/methodology/approach: Qualitative research mapped 53 social innovation initiatives with some digital use and analyzed 20 of these initiatives. Using a descriptive exploratory methodology, the study was conducted in five stages: (1) review of the literature, (2) mapping of the initiatives, (3) the selection of 20 initiatives, (4) interviews and analysis, (5) a discussion workshop on the results. Findings: The results indicate that the researched initiatives differ a little in relation to the literature. More specifically, this analysis helped perceive that in the city, (1) social innovations occur almost exclusively through the movement of civil society actors, (2) there is little to none, or only indirect articulation with governments and public policies, and (3) digital use and management remain reactive rather than strategic and are almost exclusively centered on social networks, both as a communication and management tool. Research limitations/implications: This study cannot be generalized for the city since the sample was identified by voluntary adherence of the initiatives to an internet call. Originality/value: This study contributes to knowledge on social innovations in the city of Rio de Janeiro, providing elements for debate by public and private decision makers, in addition to academic interest and shows the need for knowledge production for management rooted in the local context and reality.